"Blepharophimosis‐plus" syndromes: Frequency of systemic genetic disorders that also include blepharophimosis. (29th April 2021) - Landau Prat, Daphna; Nguyen, Brian J.; Strong, Alanna; Katowitz, William R.; Katowitz, James A.
Abstract: Background: To determine the frequency of isolated blepharophimosis‐ptosis‐epicanthus inversus syndrome (BPES) versus systemic genetic disorders in patients presenting with blepharophimosis. Methods: Retrospective clinical records review. The records of all patients with blepharophimosis seen in the Division of Ophthalmology at the Children's Hospital of Philadelphia during a 12‐year‐period (2009‐2020) were reviewed for medical history, clinical examination findings and results of genetic analyses. Results: The 135 patients identified with blepharophimosis included 72 females (53%) and 63 males (47%) whose mean ± standard deviation age at first visit was 3.5 ± 6.4 years (range 0‐39.8 years). Sixty‐seven of the patients (50%) had undergone genetic testing for FOXL2 gene mutation. Fifty‐four (81%) harboured FOXL2 gene mutations and 13 (19%) did not. Altogether, 126 patients (93%) had a final diagnosis of isolated BPES. The remaining nine (7%) had syndromic diagnoses ("blepharophimosis‐plus"), including Dubowitz syndrome ( n  = 2), Ohdo syndrome ( n  = 1), 22q11.2 duplication ( n  = 1) and 3q22 deletion ( n  = 2). Three patients with multiple congenital anomalies remain undiagnosed. Conclusions: Blepharophimosis is an eyelid feature occurring most commonly in isolation due to FOXL2 gene mutation, but can also be a harbinger of multisystem disease not exclusive to isolated BPES, as observed in 7% of cases in this series. The ophthalmologist is often the first to recognise these unique features, and must consider and rule out non‐BPES syndromes before establishing a diagnosed classic BPES. A comprehensive genetic evaluation is, therefore, indicated in all cases.